UJI EFEK ANTIBAKTERI KOMBINASI DAUN GEDI DAN DAUN KUMIS KUCING TERHADAP Staphyloccocus aureus - Karnelasatri, Karnelasatri; Trisina, Jessica; Sekeon, Yehuda Yeziel Theofilus; Febriani, Fany (Jurnal Riset Kefarmasian Indonesia, 2024)
Gedi (Abelmoschus manihot (L.) Medik) and Java tea leaves (Orthosiphon aristatus (Blume) Miq.) are known to have antibacterial activity. The combination of these two plants in inhibiting Staphylococcus aureus bacteria needs to be known to determine whether there is a synergistic effect from the combination. The synergistic effects can be demonstrated by the presence of greater antibacterial activity in the combination of both plants compared to single plant extracts. The extraction of both leaves was carried out with 96% ethanol and the maceration method. Antibacterial assay utilized the disc diffusion method with an extract concentration of 10,000 ppm and an extract ratio between two extracts was 100:0, 75:25, 50:50, 25:75, and 0:100. The positive control used was gentamicin, while the negative control used was dimethyl sulfoxide (DMSO). The resulting inhibition zones of extract combinations were 8.21 mm, 9.49 mm, 7.86 mm, 8.03 mm, and 8.74 mm, respectively. The results of data analysis using One Way ANOVA showed a sig p> 0.05, which indicated that there was no significant difference between extract comparisons, both single and combined. Based on the inhibitory zones was obtained and the statistical analysis, the combination of 10.000 ppm 96% ethanol extract of Gedi and Java tea leaves had an antibacterial activity in the weak category and did not have a synergistic effect in inhibiting the growth of Staphylococcus aureus.